From field to fork: revitalizing underutilized alliums through value chain development - Kale, Rajiv B.; Gavhane, Abhishek D.; Gadge, Shailendra S.; Gaikwad, Shivam Y.; Singh, Sharadveer; Khandagale, Kiran S.; Bhat, Rohini; Wayal, Sagar M.; Mahajan, Vijay (Frontiers in Sustainable Food Systems, 2024)
The genus Allium is a prominent member of the Amaryllidaceae family and encompasses approximately 1063 species worldwide. These diverse species vary in appearance and flavor but they share biochemical similarities. Underutilized Alliums present a promising alternative to onion and garlic in various Indian regions, given their adaptability, versatile utility, and nutraceutical properties. Their adaptation in the plains of India is a great opportunity to add medicinal and nutraceutical value to Indian cuisine. Therefore, the present study aimed to evaluate the underutilized raw Allium leaves for their sensory perception by hedonic test (n=60), consumer perceptions and willingness to purchase (n=180), and the development and validation of value chain model (n=30) to popularize these species in plains. For the various sensory attributes evaluated, Allium tuberosum Kazakhstan CGN-1587 emerged out to be the most suitable for its advancement into the consumer survey. The consumer perception study recorded 74.44% willingness to purchase of total respondents and a majority preference for consuming it in cooked form (38.30%). A value chain model of Allium tuberosum Kazakhstan CGN-1587 with supply chain agencies was subsequently developed. Validation of this value chain model was done with a panel of different stakeholders. Panellists perceived the value chain as highly valid, particularly in terms of economic feasibility (4.30 ± 0.70) and sustainability (4.20 ± 0.81). Thus, the present study provides valuable insights that can support and promote the use of underutilized Alliums in non-traditional areas of India.